Safety and immunogenicity of SARS-CoV-2 recombinant protein vaccine formulations in healthy adults: interim results of a randomised, placebo-controlled, phase 1–2, dose-ranging study. Issue 9 (September 2021) - Goepfert, Paul A; Fu, Bo; Chabanon, Anne-Laure; Bonaparte, Matthew I; Davis, Matthew G; Essink, Brandon J; Frank, Ian; Haney, Owen; Janosczyk, Helene; Keefer, Michael C; Koutsoukos, Marguerite; Kimmel, Murray A; et al.
Summary: Background: CoV2 preS dTM is a stabilised pre-fusion spike protein vaccine produced in a baculovirus expression system being developed against SARS-CoV-2. We present interim safety and immunogenicity results of the first-in-human study of the CoV2 preS dTM vaccine with two different adjuvant formulations. Methods: This phase 1–2, randomised, double-blind study is being done in healthy, SARS-CoV-2-seronegative adults in ten clinical research centres in the USA. Participants were stratified by age (18–49 years and ≥50 years) and randomly assigned using an interactive response technology system with block randomisation (blocks of varying size) to receive one dose (on day 1) or two doses (on days 1 and 22) of placebo or candidate vaccine, containing low-dose (effective dose 1·3 μg) or high-dose (2·6 μg) antigen with adjuvant AF03 (Sanofi Pasteur) or AS03 (GlaxoSmithKline) or unadjuvanted high-dose antigen (18–49 years only). Primary endpoints were safety, assessed up to day 43, and immunogenicity, measured as SARS-C0V-2 neutralising antibodies (geometric mean titres), assessed on days 1, 22, and 36 serum samples. Safety was assessed according to treatment received in the safety analysis set, which included all randomly assigned participants who received at least one dose. Neutralising antibody titres were assessed in the per-protocol analysis set for immunogenicity, which included participants who received at least one dose, met all inclusion and exclusion criteria, had no protocol deviation, had negative results in the neutralisation test at baseline, and had at least one valid post-dose serology sample. This planned interim analysis reports data up to 43 days after the first vaccination; participants in the trial will be followed up for 12 months after the last study injection. This trial is registered with ClinicalTrials.gov, NCT04537208, and is ongoing. Findings: Between Sept 3 and Sept 29, 2020, 441 individuals (299 aged 18–49 years and 142 aged ≥50 years) were randomly assigned to one of the 11 treatment groups. The interim safety analyses included 439 (>99%) of 441 randomly assigned participants (299 aged 18–49 years and 140 aged ≥50 years). Neutralising antibody titres were analysed in 326 (74%) of 441 participants (235 [79%] of 299 aged 18–49 years and 91 [64%] of 142 aged ≥50 years). There were no vaccine-related unsolicited immediate adverse events, serious adverse events, medically attended adverse events classified as severe, or adverse events of special interest. Among all study participants, solicited local and systemic reactions of any grade after two vaccine doses were reported in 81% (95% CI 61–93; 21 of 26) of participants in the low-dose plus AF03 group, 93% (84–97; 74 of 80) in the low-dose plus AS03 group, 89% (70–98; 23 of 26) in the high-dose plus AF03 group, 95% (88–99; 81 of 85) in the high-dose plus AS03 group, 29% (10–56; five of 17) in the unadjuvanted high-dose group, and 21% (8–40; six of 29) in the placebo group. A single vaccine dose did not generate neutralising antibody titres above placebo levels in any group at days 22 or 36. Among participants aged 18–49 years, neutralising antibody titres after two vaccine doses were 13·1 (95% CI 6·40–26·9) in the low-dose plus AF03 group, 20·5 (13·1–32·1) in the low-dose plus AS03 group, 43·2 (20·6–90·4) in the high-dose plus AF03 group, 75·1 (50·5–112·0) in the high-dose plus AS03 group, 5·00 (not calculated) in the unadjuvanted high-dose group, and 5·00 (not calculated) in the placebo group. Among participants aged 50 years or older, neutralising antibody titres after two vaccine doses were 8·62 (1·90–39·0) in the low-dose plus AF03 group, 12·9 (7·09–23·4) in the low-dose plus AS03 group, 12·3 (4·35–35·0) in the high-dose plus AF03 group, 52·3 (25·3–108·0) in the high-dose plus AS03 group, and 5·00 (not calculated) in the placebo group. Interpretation: The lower than expected immune responses, especially in the older age groups, and the high reactogenicity after dose two were probably due to higher than anticipated host-cell protein content and lower than planned antigen doses in the formulations tested, which was discovered during characterisation studies on the final bulk drug substance. Further development of the AS03-adjuvanted candidate vaccine will focus on identifying the optimal antigen formulation and dose. Funding: Sanofi Pasteur and Biomedical Advanced Research and Development Authority.